A Review of Medium Access Control Protocols in Next Generation Wireless Networks (IEEE 802.16) - Rehman, Faheem ur; Malik, Shahzad Ali (JISR management and social sciences & economics, 2007)
The IEEE 802.16 standard for broadband wireless access has recently been approved. It is an emerging global broadband wireless access standard capable of delivering multiple megabits of shared data throughput supporting fixed, portable, and mobile operation. The standard offers a great deal of design flexibility including support for licensed and licenseexempt frequency bands, channel widths ranging from 1.25 to 20 MHz, Quality of Service (QoS) establishment on a per-connection basis, strong security primitives, multicast support, and low latency/low packet loss handovers. This paper discusses the main features of the various IEEE 802.16 standards with emphasis on the MAC protocol. The focus is on analyzing the differences between MAC layer implementations in several version of the standard like 802.16, 802.16a and 802.16e. This review can be used as the foundation to conduct detailed performance analysis of the emerging WIMAX/802.16 systems.